Listening Activity in the Life of Rural and Urban Students - Nadrah, Nadrah; Arono, Arono; Villia, Ade Sissca (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
he gap in listening skills between students in rural and urban areas is still a problem that has not been resolved comprehensively. This study aims to identify and analyze the differences in listening skills of students living in rural and urban areas and the factors that influence these skills. The research method used was a quantitative survey with a descriptive approach, involving 125 students through propositional sampling in Bengkulu from various universities in rural and urban areas in Bengkulu Province. Data were collected through questionnaires and interviews, then analysed using simple descriptive statistics. The results of the study showed that the condition of student listening activities between rural and urban areas from the average aspect was no different, in the sufficient category with an average range of 2.61-3.40 (3.32 rural; 3.36 urban). Aspects of media access, difficulty, and materials showed differences in categories in the aspect of listening materials in rural areas, namely good/supportive (3.47). Urban students tend to have difficulty listening effectively because they are exposed to too much information from various digital platforms, which reduces their concentration and understanding. Rural areas tend to listen more to local story-based content and traditional themes, which limits their exposure to global issues and modern content. Factors such as access to educational resources, social environment, and family support have been found to play an important role in shaping students' listening skills.